2014
DOI: 10.2960/j.v46.m695
|View full text |Cite
|
Sign up to set email alerts
|

Decadal Distribution and Abundance Trends for the Late Stage Copepodites of Pseudocalanus spp. (Copepoda: Calanoida) in the US Northeast Continental Shelf Ecosystem.

Abstract: The average annual cycle of abundance and the bimonthly distributions of the copepod Pseudocalanus spp. are described for U

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…For example, there is evidence for phytoplankton productivity regime shifts over the past 30 yr (Kane 2011b, Greene et al 2013, and regimes in zooplankton biomass and community structure are well documented (Kane 2007, 2011a, 2014, Turner et al 2011, Greene et al 2013, Bi et al 2014, Morse et al 2017. However, there is less evidence for regime shifts at higher trophic levels, particularly in fish recruitment.…”
Section: Introductionmentioning
confidence: 99%
“…For example, there is evidence for phytoplankton productivity regime shifts over the past 30 yr (Kane 2011b, Greene et al 2013, and regimes in zooplankton biomass and community structure are well documented (Kane 2007, 2011a, 2014, Turner et al 2011, Greene et al 2013, Bi et al 2014, Morse et al 2017. However, there is less evidence for regime shifts at higher trophic levels, particularly in fish recruitment.…”
Section: Introductionmentioning
confidence: 99%
“…(Erikson et al . ; Kane ), which are the preferred prey of these economically important fish species (Petrik et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…The projected increase in C. typicus populations linked to increasing temperatures (Stegert et al 2012) could also have a significant impact on ecosystems and fisheries, especially if combined with a decrease in the abundances of other copepod species, such as Pseudocalanus spp. (Erikson et al 2014;Kane 2014), which are the preferred prey of these economically important fish species (Petrik et al 2009). Centropages typicus is not, however, a preferred prey item of haddock and cod larvae (Petrik et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The species cannot be reliably distinguished using morphological characters and even recent studies have reported the combined abundances of the sibling species (e.g., O'Brien et al, 2013;Kane, 2007Kane, , 2014.…”
Section: Introductionmentioning
confidence: 99%